Expression of classical mediators in hearts of rats with hepatic dysfunction - Jarkovska, Dagmar; Bludovska, Monika; Mistrova, Eliska; Krizkova, Vera; Kotyzova, Dana; Kubikova, Tereza; Slavikova, Jana; Erek, Sumeyye Nur; Djordjevic, Aleksandar; Chottova Dvorakova, Magdalena (Canadian journal of physiology and pharmacology, 2017)
Liver cirrhosis is associated with impairment of cardiovascular function including alterations of the heart innervation, humoral and nervous dysregulation, changes in systemic circulation and electrophysiological abnormalities. Choline acetyltransferase (ChAT), enzyme forming acetylcholine, tyrosine hydroxylase (TH), and dopamine-β-hydroxylase (DBH), enzymes participating in noradrenaline synthesis, are responsible for the production of classical neurotransmitters, and atrial natriuretic peptide (ANP) is produced by cardiomyocytes. The aim of this study was to evaluate the influence of experimentally induced hepatic dysfunction on the expression of proANP, ChAT, TH, and DBH in the heart. Hepatic dysfunction was induced by application of thioacetamide (TAA) or by ligation of bile duct. Biochemical parameters of hepatic injury and levels of peroxidation in the liver and heart were measured. Liver enzymes measured in the plasma were significantly elevated. Cardiac level of peroxidation was increased in operated but not TAA group animals. In the left atrium of operated rats, the expression of TH and DBH was lower, while expression of ChAT remained unchanged. In TAA group, no significant differences in the expression of the genes compared to controls were observed. Liver injury induced by ligation leads to an imbalance in the intracardiac innervation, which might impair nervous control of the heart.
Keywords: Gene Expression Regulation; Liver Cirrhosis; oxidační stres; catecholamines; cirrhotic cardiomyopathy; Male; dopamin-beta-hydroxylasa; catécholamines; cœur; srdce; lipid peroxidation; Myocardium; mužské pohlaví; bile duct ligation; thioacétamide; tyrosin-3-monooxygenasa; intracardiac nervous system; krysa rodu Rattus; Atrial Natriuretic Factor; heart; système nerveux intracardiaque; Animals; Tyrosine 3-Monooxygenase; akční potenciály; Action Potentials; jaterní cirhóza; játra; cardiomyopathie cirrhotique; ligature du conduit cholédoque; peroxydation lipidique; zvířata; regulace genové exprese; Rats; Dopamine beta-Hydroxylase; thioacetamide; atriální natriuretický faktor; peroxidace lipidů; Muscle Contraction; Lipid Peroxidation; Liver; svalová kontrakce; Heart; Oxidative Stress; myokard